Metataxonomic and Metabolic Impact of Fecal Microbiota Transplantation From Patients With Pancreatic Cancer Into Germ-Free Mice: A Pilot Study - Genton, Laurence; Lazarevic, Vladimir; Stojanovic, Ozren; Spiljar, Martina; Djaafar, Souad; Koessler, Thibaud; Dutoit, Valérie; Gaïa, Nadia; Mareschal, Julie; Macpherson, Andrew James; Herrmann, Francois; Trajkovski, Mirko; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Body weight (BW) loss is prevalent in patients with pancreatic cancer (PC). Gut microbiota affects BW and is known to directly shape the host immune responses and antitumor immunity. This pilot study evaluated the link between gut microbiota, metabolic parameters and inflammatory/immune parameters, through the fecal material transplantation (FMT) of PC patients and healthy volunteers into germ-free (GF) mice. Methods We transplanted the feces from five PC patients and five age- and gender-matched healthy volunteers into two GF mice each. Mouse BW and energy intake were measured every 1-5 days, oral glucose on day 21, insulin tolerance on day 26, fecal bacterial taxonomic profile by 16S rRNA gene sequencing on day 5, 10, 15 and 30, and gut-associated lymphoid tissue T cells, plasma cytokines and weights of fat and muscle mass at sacrifice (day 34). Results are presented as mean ± SD. The continuous parameters of mice groups were compared by linear univariate regressions, and their bacterial communities by Principal Coordinates Analysis (PCoA), Bray-Curtis similarity and ANCOM test. Results Recipients of feces from PC patients and healthy volunteers had similar BW gain and food intake. Visceral fat was lower in recipients of feces from PC patients than from healthy individuals (0.72 ± 0.17 vs. 0.92 ± 0.14 g; coeff -0.19, 95% CI -0.38, -0.02, p=0.035). The other non-metataxonomic parameters did not differ between groups. In PCoA, microbiota from PC patients clustered apart from those of healthy volunteers and the same pattern was observed in transplanted mice. The proportions of Clostridium bolteae, Clostridium scindens, Clostridium_g24_unclassified and Phascolarctobacterium faecium were higher, while those of Alistipes obesi, Lachnospiraceae PAC000196_s and Coriobacteriaceae_unclassified species were lower in PC patients and in mice transplanted with the feces from these patients. Conclusion In this pilot study, FMT from PC patients was associated with a decrease in visceral fat as compared to FMT from healthy individuals. Some of the differences in fecal microbiota between PC and control samples are common to humans and mice. Further research is required to confirm that feces contain elements involved in metabolic and immune alterations.